Chronic pain in later life: a review of current issues and challenges. (August 2011) - Schofield, Pat; Clarke, Amanda; Jones, Derek; Martin, Denis; McNamee, Paul; Smith, Blair
The effects of aging present a major medical challenge in the 21st century, which will cause fundamental changes in demography. By 2031, it is estimated that 22% of the UK population will be aged over 65 years, and there will be more people in this age group than aged under 25 years. As well as implications for infrastructure and productivity, this change will alter the prevalence and impact of many illnesses and pathologies. The research priorities of many of the major funding bodies reflect this challenge. The Medical Research Council in the UK, for example, leads the Lifelong Health and Wellbeing program on behalf of all the country''s research councils. This initiative aims to identify factors that affect or improve health in later life, to inform relevant policy and practice. The Wellcome Trust lists the investigation of development, aging and chronic disease as one of its five major research challenges, and the European Commission presents the health of the aging population as one of its three overarching issues of the Health Theme in its 7th Framework Program of research. Chronic pain is a major health condition associated with aging, whose management (pharmacological and nonpharmacological) is generally unsatisfactory. The International Association for the Study of Pain designated 2006/07 as its Global Year Against Pain in Older Adults. This article reviews the relevance of existing and potential research on the assessment and management of chronic pain in older adults.